Delayed PCI 12 Hours after the Onset of Symptoms Is Associated with Improved Outcomes for Patients with ST-Segment Elevation Myocardial Infarction: A Real-World Study - Wen-Juan Xiu; Hai-Tao Yang; Ying-Ying Zheng; Yi-Tong Ma; Xiang Xie (Journal of Interventional Cardiology)
Background. Primary percutaneous coronary intervention (PPCI) plays a pivotal role in the treatment of ST-segment elevation myocardial infarction (STEMI). However, it remains controversial whether PCI delayed beyond the recommended time window of 12 h after the onset of symptoms is applicable to STEMI. Objective. The acute myocardial infarction (AMI) registration study in Xinjiang, China, is a real-world clinical trial (retrospective cohort study) that includes hospitalized patients. The purpose of this study was to compare delayed PCI and medication therapy beyond the recommended time window of 12 h after the onset of symptoms on the outcomes of STEMI patients. Methods and Results. From May 2012 to December 2015, a total of 1072 STEMI patients received delayed PCI (n=594) or standard medication therapy (MT) (n=478) more than 12 h after the onset of symptoms. The number of all-cause deaths in the delayed PCI group and that in the MT group were 55 (9.3%) and 138 (28.9%), respectively, and a significant difference between the groups was indicated for this variable (P<0.001). The number of cardiac deaths in the delayed PCI group and that in the medication therapy group were 47 (7.9%) and 120 (25.1%), respectively, and a significant difference between the groups was indicated for this variable (P<0.001). We also found that the MACE incidence in the delayed PCI group was significantly higher than it was in the MT group (32.2% versus 43.5%, P<0.001). Propensity score matching (PSM) analyses remained significant differences between the delayed PCI group and the MT group, respectively, in all-cause deaths (9.3% versus 25.8%, P<0.001) and cardiac death (8.7% versus 21.6%, P<0.001). Conclusion. Compared to medication therapy, PCI for STEMI delayed beyond 12 h after the onset of symptoms can better reduce mortality and the incidence of MACEs. Trial Registration. This study is registered with the following: Trial Registration: clinicaltrials.gov; Identifier: NCT02737956.